Evaluating perceptions of Arabic teaching and curriculum integration of dialect - Tariq Mohammed Farghal; Mohammad Abed Latif Mohammad Smadi; Hadieh Yousef; Sara Tamimi; Sireen Afara (Institute of Advanced Engineering and Science, 2026)
This study investigates the attitudes of foreign students at Amman Arab University (AAU) in Jordan toward learning Arabic, shedding light on the teaching approaches of Arabic dialect, particularly Jordanian Arabic (JA), while exploring their perspective on Arabic diglossia. The study examines faculty member’s academic views specifically those of the English department and basic sciences, incorporating linguistics, translation scholars, and Arabic lecturers. The findings show that while students stigmatize the Jordanian dialect, recognizing its grammar inferiority to modern standard Arabic (MSA), they contradictorily express a keen interest in learning the dialect due to its cultural and practical relevance to Arabic-speaking societies. Contrarily and strikingly, faculty members, despite their tolerance of the vernacular in informal contexts, hold an opposing opinion that prevents the inclusion of an Arabic curriculum for non-native speakers. Moreover, the study affirms the divergence in perspectives which showcases the tension between the traditional view of H variety being the “proper” variety of the language and the practical demand of the dialect for effective communications in the Arab world. While emphasizing the significance of presenting these contradictions in Arabic language pedagogy, the study introduces the integration of dialect teaching alongside MSA to simply align with students’ linguistic needs.